Peran Civil Society dalam Menumbuhkan Sikap Toleransi Beragama di Indonesia - Hakki Fajriando (Badan Strategi Kebijakan Hukum, 2014)
This research was conducted in Aceh, West Kalimantan, Central Sulawesi and Maluku. The goal is to get an overview of the role of civil society, as well as to analyze the synergy between government policies and the activities of civil society in fostering religious tolerance. The results of this research are expected to provide insights for central and local government policy making, especially those related with efforts to foster communal harmony and inter-religious tolerance in Indonesia. The method used in this research is a combination of quantitative and qualitative methods. Primary data collection was done by using in-depth interviews and distributing questionnaires, while secondary data were obtained through library studies. Every data obtained as such were processed and analyzed with the ultimate goal of answering the research question. The development in the four provinces reveals the important role of community leaders in the creation of supportive conditions for inter-religious tolerance and communal harmony. Various community organizations have also asserted their roles in the efforts to foster a culture of inter-religious tolerance. NGOs, as part of civil society organizations, have also showed their awareness to the importance of creating social cohesion within the community.